Biblical women and Jewish daily life in the Middle Ages - Baumgarten, Elisheva (Jewish culture and contexts., 2022)
In Biblical Women and Jewish Daily Life in the Middle Ages, Elisheva Baumgarten examines how medieval Jewish engagement with the Bible--especially in the tellings, retellings, and illustrations of stories of women--offers a window onto aspects of the daily lives and cultural mentalités of Ashkenazic Jews in the High Middle Ages.